1)
=================================================
2)
3)
4)
5)
6)
7)
8)
1)(2m+1)(a+b)
2)(2a+1)(x+y)
3)(4x-1)(m-n)
4)(x+1)(a-b)
5)(5x-1)(a+b)
6)(4y-1)(k-p)
7)(3m-1)(x+y)
8)(2a-1)(x-y)
1)![2m(a+b)+a+b=2m(a+b)+1(a+b)=(a+b)(2m+1)](/tpl/images/0040/8489/e7086.png)
=================================================
2)![2a(x+y)+x+y=2a(x+y)+1(x+y)=(x+y)(2a+1)](/tpl/images/0040/8489/8c894.png)
=================================================
3)![4x(m-n)-m+n=4x(m-n)+(-m+n)=4x(m-n)-1(m-n)=(m-n)(4x-1)](/tpl/images/0040/8489/64c72.png)
=================================================
4)![x(a-b)+a-b=x(a-b)+1(a-b)=(a-b)(x+1)](/tpl/images/0040/8489/9bacf.png)
=================================================
5)![5x(a+b)-a-b=5x(a+b)+(-a-b)=5x(a+b)-1(a+b)=(a+b)(5x-1)](/tpl/images/0040/8489/bd613.png)
=================================================
6)![4y(k-p)-k+p=4y(k-p)+(-k+p)=4y(k-p)-1(k-p)=(k-p)(4y-1)](/tpl/images/0040/8489/e381d.png)
=================================================
7)![3m(x+y)-x-y=3m(x+y)+(-x-y)=3m(x+y)-1(x+y)=(x+y)(3m-1)](/tpl/images/0040/8489/31909.png)
=================================================
8)![2a(x-y)-x+y=2a(x-y)+(-x+y)=2a(x-y)-1(x-y)=(x-y)(2a-1)](/tpl/images/0040/8489/78418.png)
1)(2m+1)(a+b)
2)(2a+1)(x+y)
3)(4x-1)(m-n)
4)(x+1)(a-b)
5)(5x-1)(a+b)
6)(4y-1)(k-p)
7)(3m-1)(x+y)
8)(2a-1)(x-y)